2016
DOI: 10.1016/j.jvs.2015.08.110
|View full text |Cite
|
Sign up to set email alerts
|

Aortic curvature as a predictor of intraoperative type Ia endoleak

Abstract: Together with aortic neck calcification, aortic curvature appears to be the best predictor of intraoperative type Ia endoleak, as expressed within the juxtarenal aortic neck, the aneurysm sac, and the terminal aorta. Aortic neck angulation was not a predictor for acute failure. Aortic curvature may provide a better anatomic characteristic to define patients at risk for early complications after endovascular aneurysm repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…A previous study also identified curvature expressed over the infrarenal neck and the aneurysm sac as a predictor for intraoperative type Ia endoleak. 10 Contrary to intraoperative type Ia endoleaks, maximum curvature over the aneurysm sac was more predictive for late failure than average curvature. The maximum curvature over the trajectory of the aneurysm sac was mostly located in the proximal part of the sac, with a median distance of 43.6 mm (IQR 20.8-68.6) below the lower renal artery origin for the complication cohort.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A previous study also identified curvature expressed over the infrarenal neck and the aneurysm sac as a predictor for intraoperative type Ia endoleak. 10 Contrary to intraoperative type Ia endoleaks, maximum curvature over the aneurysm sac was more predictive for late failure than average curvature. The maximum curvature over the trajectory of the aneurysm sac was mostly located in the proximal part of the sac, with a median distance of 43.6 mm (IQR 20.8-68.6) below the lower renal artery origin for the complication cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Since early and late complications are often combined in the literature, this study, together with our earlier publication considering intraoperative type Ia endoleak, 10 adds to the understanding of the association between morphological aortic parameters and the onset of complications.…”
Section: Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…We therefore propose to modify the previous risk-stratified surveillance protocol, because patients with increased risk may benefit from a timely second postoperative CTA scan. These high-risk patients include those with challenging pre-operative anatomy, such as short neck length (<10 mm), large neck diameter (>30 mm), large aortic curvature (>50 m −1 ), large aneurysm sac diameter (>65 mm), or large CIA diameter (>19 mm) [21][22][23][24][25][26], those treated outside indications for use [27], those with any endoleak or insufficient proximal or distal seal (<10 mm) on the first postoperative CTA [4,5], and those where suspicion of complications arises during follow-up, such as >5 mm aneurysm growth. In these patients, a second postoperative CTA is advised within 2 years, on which endograft apposition and position should be re-assessed and compared with the baseline values on the first postoperative CTA scan to allow detection of continuous (subtle) deterioration of apposition over time.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Subsequently, the same authors reported that aortic curvature appeared to be the best predictor of intraoperative type Ia endoleak along with aortic neck calcification, whereas aortic neck angulation was not. 17…”
mentioning
confidence: 99%